(untitled) (Research, Society and Development, 2021)
Brachycephalic syndrome in dogs and cats is directly linked to obstructive processes that occur as a result of important anatomical deformities of the anterior airways commonly found in these animals. These changes impact the physiological functions of the respiratory and digestive cardiovasculares systems, among others, significantly compromising the well-being and quality of life of these animals. The present work aims to present a literature review showing the clinical and surgical treatment of brachycephalic syndrome, where it could be concluded that despite the severity of this disease there is the possibility of clinical and surgical treatment with indication of corrections of multiple obstructive anatomical changes, being the prognosis favorable, especially for dogs that had their treatment started early, significantly improving the welfare and quality of life of these animals.